lim(x→0)=(1/x^2-cot^2x)lim(x→∞)=[(2+x)e^(1/x)-x]

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/13 20:59:32
lim(x→0)=(1/x^2-cot^2x)lim(x→∞)=[(2+x)e^(1/x)-x]

lim(x→0)=(1/x^2-cot^2x)lim(x→∞)=[(2+x)e^(1/x)-x]
lim(x→0)=(1/x^2-cot^2x)
lim(x→∞)=[(2+x)e^(1/x)-x]

lim(x→0)=(1/x^2-cot^2x)lim(x→∞)=[(2+x)e^(1/x)-x]
lim(x→0)=(1/x^2-cot^2x)
=lim(x→0)=(1/x^2-1/tan²x)
=lim(x->0)(tan²x-x²)/x²tan²x
=lim(x->0)(tan²x-x²)/x^4
=lim(x->0)(tanx+x)(tanx-x)/x^4
=lim(x->0)(tanx+x)/x*lim(x->0)(tanx-x)/x³
=2lim(x->0)(sec²x-1)/3x²
=2lim(x->0)(tan²x)/3x²
=2/3
lim(x→∞)=[(2+x)e^(1/x)-x]
令x=1/t
原式=lim(t->0)[(2+1/t)e^t-1/t]
=lim(t->0)[(2t+1)e^t-1]/t
=lim(t->0)[(2t+1)e^t+2e^t]/1
=1+2
=3

^是啥?

1)原式= lim(tan²x -x²)/ x²tan²x
= lim(tanx +x)(tanx -x) / x²tan²x 再把分母的tan²x换为x²
=lim (tanx +x)/(x) *lim (tanx -x)/ (x³) ...

全部展开

1)原式= lim(tan²x -x²)/ x²tan²x
= lim(tanx +x)(tanx -x) / x²tan²x 再把分母的tan²x换为x²
=lim (tanx +x)/(x) *lim (tanx -x)/ (x³) 后面一个lim用洛必达法
= 2 lim (sec²x-1)/3x²
=2lim tan²x / 3x²
= 2/3
2)令1/x=t ,t趋于0
原式=lim ((2+1/t)e^t -1/t) 通分
=lim [(2t+1)e^t -1] /t 洛必达法
=lim (2t+3)e^t
=3

收起